Effect of site elevation and soil depth on the biomass and carbon, nitrogen, and phosphorus stocks of roots in planted Kandelia obovata mangrove forests. Issue 3 (9th June 2022) - Chen, Jiahui; Huang, Yingying; Chen, Guangcheng; Zhu, Heng; Qiu, Yue; Ye, Yong
Abstract : Site elevation is one of the most important factors for successful mangrove restoration. Understanding how site elevation influences mangrove roots is critical for evaluating mangrove primary productivity, carbon dynamics and nutrient cycles. Root biomass and organic carbon (OC), total nitrogen (N), and total phosphorus (P) stocks were compared through an in situ experiment among 11‐year‐old Kandelia obovata mangrove forests planted under three intertidal elevations. Compared with site upper elevation, biomass of total root, live root, dead root, fine root, and coarse root decreased approximately 74.62, 79.82, 26.65, 42.52, and 87.09%, respectively, but contribution rates of fine root to total root increased 35.40% at site lower elevation. Biomass of total root and fine root at the three sites decreased with soil depth increases. Stocks of OC, N, and P in the total root decreased approximately 70, 52.92, and 47.30% from site upper elevation to site lower elevation owing to decreases in the total root biomass. Stocks of OC, N, and P in the total root and fine root also decreased with soil depth increases, while only OC stock of coarse root had a decreasing trend with soil depth increases. These indicated that decreases in site elevation will reduce mangrove primary productivity, carbon dynamics, and nutrient cycles due to decreases in root biomass. For K.obovata forests, upper elevation should be used in the future mangrove forest restoration projects to improve mangrove blue carbon capability.